Use of cocoa ethanolic extract for treatment of Staphylococcal infection in rabbit-skin model - Ariza Budi Tunjung-Sari; Teguh Wahyudi; Diana Chusna Mufida; Mekania Tamarizki; Desyana Perwitahati; Ihda Kartika Syamsuddin; Misnawi Jati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
In  septic  condition,  the  skin  normal  flora  Staphylococcal  spp.  may  trigger local  and  sistemic  skin  infection.  In  this  study  antibacterial  activity  of  cocoa ethanolic  extract  (CEE)  against  Staphylococcus  aureus  and  Staphylococcus epidermidis infections  was  observed  in  vitro  and  in  vivo.  Ethanolic  extract  from unfermented  cocoa  beans  was  prepared  as  solution  in  the  in  vitro  testing,  while for  in  vivo  testing  the  extract  was  prepared  as  cream.  Agar  well  diffusion  assay showed  that  CEE  ranging  from  7.8  mg/mL  to  1000  mg/mL  demonstrated  inhibitory  activity  against  growth  of  either  S.  aureus  and  S.  epidermidis. Inhibitory activity  of  CEE  was  in  concentration  dependent  manner,  and  was  less  potential than either cephalexin 4 x 10 -3 mg/mL or cefotaxime 8 x 10 -3 mg/mL. Linear regression of CEE concentration plotted against inhibition zone values ha dpredicted the minimum inhibitory  concentrations  (MIC)  of  CEE  towards  S.  aureus  and  S.  epidermidis were at 341.9 mg/mL and 359.7 mg/mL, respectively. Topical application of cream containing  CEE  at  several  concentrations  (2%,  4%,  and  8%)  demonstrated  healing properties  towards  incision  wound  infected  with  S.  aureus and  S.  epidermidis cultures in rabbit-skin model. CEE cream promoted wound contraction and higher recovery  rate  than  of  base  cream  (negative  control)  but  lower  than  mupirocin 2%  cream.  In  S.  aureus and  S.  epidermidis  infected  wound  models,  CEE  cream 8%  improved  wound  recovery  to  72.7%  and  86.1%  from  original  rates  of  23.5% and 34.7% (base cream application). Catechin and procyanidis are suggested playing roles in  alleviation of wound inflammation and stimulation of extracellular matrix accumulation,  thus  accelerate  the  wound  healing  process.  This  study  proposes utilization  of  cocoa  bean  as  source  of  active  ingredient  for  skin  care  products.